2021
DOI: 10.1101/2021.05.04.442648
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunolocalization studies of vimentin and ACE2 on the surface of cells exposed to SARS-CoV-2 Spike proteins

Abstract: The Spike protein from SARS-CoV-2 mediates docking of the virus onto cells and contributes to viral invasion. Several cellular receptors are involved in SARS-CoV-2 Spike docking at the cell surface, including ACE2 and neuropilin. The intermediate filament protein vimentin has been reported to be present at the surface of certain cells and act as a co-receptor for several viruses; furthermore, its potential involvement in interactions with Spike proteins has been proposed. Here we have explored the binding of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 92 publications
1
2
0
Order By: Relevance
“…In the present study, we show that vimentin is released from the back of these TNF-α–activated macrophages, and that this polarised release is enhanced by the macrophage activation. Moreover, using confocal, TIRF and SEM, we have confirmed that the structure of the secreted vimentin is not filamentous, as is its intracellular counterpart, but is in form of fragments, as indicated in recent studies (Suprewicz et al, Lalioti et al, 2021 ). Nevertheless, further confirmation of data from GFP-vimentin HL60 is needed as it may not behave identical to endogenous vimentin.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, we show that vimentin is released from the back of these TNF-α–activated macrophages, and that this polarised release is enhanced by the macrophage activation. Moreover, using confocal, TIRF and SEM, we have confirmed that the structure of the secreted vimentin is not filamentous, as is its intracellular counterpart, but is in form of fragments, as indicated in recent studies (Suprewicz et al, Lalioti et al, 2021 ). Nevertheless, further confirmation of data from GFP-vimentin HL60 is needed as it may not behave identical to endogenous vimentin.…”
Section: Discussionsupporting
confidence: 83%
“…The spike of SARS-CoV-2 evolves faster than other genomic regions via both point mutations [ 41 , 42 ] and recombination [ 43 ]. Therefore, several evolutionary scenarios for the future trajectory of SARS-CoV-2 [ 44 ] show that this pandemic may not yet be over.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in these procedures are specified in the corresponding figure legends. Additional technical details, controls and limitations of the tools employed are available as preprint 42 .…”
Section: Methodsmentioning
confidence: 99%